Therapeutic Outcomes of Secukinumab 300 mg in Severe Psoriasis Vulgaris with Metabolic Comorbidities: A Retrospective Cohort Study in Bali - Prima Sanjiwani Saraswati Sudarsa; Mario Korwa; Nyoman Suryawati (HM Publisher, 2026)
Background: Psoriasis vulgaris is a systemic inflammatory disease increasingly prevalent in Southeast Asia, often complicated by metabolic syndrome. While Secukinumab, an IL-17A inhibitor, is established in Western cohorts, real-world data on its efficacy in Indonesian populations with high adiposity burdens are scarce. This study evaluates the therapeutic response and safety of Secukinumab 300 mg in a Balinese cohort characterized by severe disease and metabolic risk factors. Methods: We conducted a retrospective cohort study at a tertiary referral center in Bali from January 2023 to December 2024. The study included 39 adult patients with moderate-to-severe psoriasis treated with Secukinumab 300 mg. The primary endpoint was the proportion of patients achieving a 75% reduction in the Psoriasis Area and Severity Index (PASI 75) at Week 17. Fisher’s Exact Test was employed to analyze response differences between obese and non-obese subgroups. Results: The cohort exhibited a high systemic burden: 44.2% were obese (Body Mass Index greater than or equal to 25 kg/m2), and 53.8% had concomitant psoriatic arthritis. Baseline disease severity was high with a median body surface area of 25.0%. At week 17, 32 patients (82.1%; 95% confidence interval: 67.3–91.0%) achieved PASI 75. Subgroup analysis revealed no statistically significant difference in response rates between obese and non-obese patients (p > 0.99), suggesting efficacy is maintained despite metabolic burden. No severe adverse events or discontinuations were documented in the medical records. Conclusion: Secukinumab 300 mg demonstrates substantial efficacy in an Indonesian population with a severe phenotypic profile, maintaining therapeutic clearance in metabolically compromised patients. The safety profile appears favorable, though limited by retrospective data capture.